2001
DOI: 10.1097/00006534-200108000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Mirror, Mirror on the Wall: When the Postoperative Reflection Does Not Meet Patientsʼ Expectations

Abstract: In this study, the authors investigated the physiologic effects of the altered body composition that results from surgical removal of large amounts of subcutaneous adipose tissue. Fourteen women with body mass indexes of greater than > 27 kg/m2 underwent measurements of fasting plasma insulin, triglycerides, cholesterol, body composition by dual-energy x-ray absorptiometry (DXA), resting energy expenditure, and blood pressure before and after undergoing large-volume ultrasound-assisted liposuction. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…This reinforces the mantra that there needs to be proper preoperative patient selection and preoperative discussion of realistic postoperative results and expectations. 18 Complete analysis of the data demonstrated that among all the variables tested by this survey, weight gain was the most pivotal. In a separate publication, the relationship of weight gain, postoperative patient lifestyle choices, and satisfaction will be discussed.…”
Section: Conducted Inmentioning
confidence: 85%
“…This reinforces the mantra that there needs to be proper preoperative patient selection and preoperative discussion of realistic postoperative results and expectations. 18 Complete analysis of the data demonstrated that among all the variables tested by this survey, weight gain was the most pivotal. In a separate publication, the relationship of weight gain, postoperative patient lifestyle choices, and satisfaction will be discussed.…”
Section: Conducted Inmentioning
confidence: 85%
“…Factors such as personal preference, aversion to medical intervention, and professional recommendations likely affect the decision to undergo treatment. Because patients' perspectives have become a major component of assessing outcome, patients' expectations also have become incorporated in the creation of quality reporting schemes [11,13,20,27,28,37]. Identification of expectations offers tangible participation in a shared decision-making process when an array of different treatment options is available.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of expectations offers tangible participation in a shared decision-making process when an array of different treatment options is available. Understanding what generates or influences patients' expectations and identifying what patients expect may allow greater convergence of the priorities and goals held by patients and surgeons [13,20,27,28,37]. This may be fundamental to optimizing patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' expectations vary widely, are the product of the patient's personality and experiences, and can often be influenced by the surgeon during the consultation. 10,34 The importance of understanding and guiding patient expectations cannot be overstated. Mismanaged patient expectations are The importance of each factor in determining patient suitability for surgery is rated on a 7-point scale: 1 ϭ least important, 7 ϭ most important.…”
Section: Discussionmentioning
confidence: 99%